An effective approach to improve ethanol productivity by simultaneous saccharification and fermentation of rice straw. Issue 10 (9th August 2018) - Xie, Taiping; Xu, Longjun; Liu, Chenglun; Bi, Zhiming
ABSTRACT: Fuel ethanol was produced using rice straw with the simultaneous saccharification and fermentation (SSF) method. The influence of cellulose liquefaction pretreatment and Fe 2+ quantity on ethanol productivity was investigated in detail. At the same time, the optimized conditions including fermentation temperature, Fe 2+ amount, yeast inoculation quantity, and the inoculated cellulose enzyme dosage in the SSF process were systematically investigated by analyzing fuel ethanol yield. The result indicated that fuel ethanol yield was 0.319 g per gram rice straw by SSF approach when appropriate amount of Fe 2+ was added into the reaction system. The optimal technology parameters were: fermenting temperature of 36°C, Fe 2+ amount of 4 mg · g −1, inoculating proportion of 20%, cellulose enzyme of 20 IU · g −1, and Pachysolen tannophilu / saecharomyces cerevisiae of 1:2 ratio. The ethanol yield under the best conditions was larger than that of the control group. We hope that this research can facilitate to achieve large-scale comprehensive utilization for rice straw.